SHAPING THE STOCK PORTFOLIO BY THE INVESTMENT RATING METHOD - Svyatoslav N. Digo; Aleksandra M. Sokolova (Вестник Российского экономического университета имени Г. В. Плеханова)
For the last five years capitalization of joint stock companies in Russia nearly doubled while the major indicator of stock market  development, i. e. MISEX index – increased more than in 1,5 times.  In spite of such favourable conditions for the development of  portfolio investment mutual investment funds, whose investment is  mainly shares demonstrate low effectiveness. In 2015 the growth in  investment funds profitability showed 30,82% (in average), while  MISEX index grew by 28,72%. If we take into account that  commission rates with purchase and redemption reach 3,5%, while  with purchase of exchange investment fund – 1%, then investor  profitability, who entrusted his/her money to investment company or just invested it in index will be equal. Thus securities market needs more effective methods and algorithms of shaping the stock portfolio, as investor’s expectations of getting profits could be met  only in case of professional choice of investment projects. The article puts forward a new express method of selecting shares to the  portfolio called the method of investment rating. This method is  based on developing logistic regression. It provides an opportunity to analyze share price of all issuers with the help of the programmed  algorithm taking into account not only principle shares’  characteristics (risk and profitability) but the impact of other variables connected with finance and business work of the issuer and his market figures. The authors described economic and mathematic  aspect of the process of giving an investment grade and tested the method of investment rating on the Russian securities market.